تصميم وانجاز مجفف بالغاز الطبيعي - يونس, قادي; جابر, بن عمر (جامعة الشهيد حمه لخضر الوادي, 2023)
تهدف هذه الدراسة إلى حل مشكل كبير تعاني منه معظم الدول وخاصة الجزائر في قلة طرق حفظ المحاصيل الزراعية عند حدوث فائض في الانتاج، نقترح استعمال المجففات التي تعمل بالغاز الطبيعي. وفي هذه الدراسة، قمنا بعمل تجريبي لتصميم مجفف بالغاز الطبيعي لمعرفة مدى كفاءته. تمت الدراسة على مرحلتين تجربتين، الأولى في يوم 23 ماي 2023 خصصت لتصميم المجفف، فكانت النتائج جد مرضية، أما في المرحلة الثانية، تم تجفيف مادة الطماطم المعروفة بالإنتاج المحلى الوفير، حيث كذلك تمت عملية التجفيف في غضون 6 ساعات فقط، أي نزع ما يقارب نسبة 72.31% من محتوى الرطوبة. This study aims to solve a major problem that most countries, especially Algeria, suffer from in the lack of methods for preserving agricultural crops when there is a surplus in production. We suggest the use of natural gas dryers. In this study, we conducted an experimental work to design a natural gas dryer to see its efficiency. The study was carried out in two experimental phases, the first on May 23, 2023 was devoted to the design of the dryer, and the results were very satisfactory. In the second phase, the tomato material known for abundant local production was dried, where the drying process was also completed within 6 hours only, i.e. the removal of approximately 72.31% moisture content.
مذكرات ماستر تخصص الطاقات المتجددة في الميكانيك
Keywords: التجفيف، المجففات، تصميم المجفف، تجفيف الطماطم; drying, desiccants, dryer design, tomato drying.